Human Resource Management Practices for Effective Organizational Change: A Review of Research in Western and Non-Western Countries - AL-NAKEEB Ahmed A. R.; GHADI Mohammed Yasin (Foundations of Management)
Organizational change (OC) initiatives require effective human resource management practices (HRMPs). This review analyzes recent research on the role of HRMPs in OC, focusing on major trends and differences between Western and non-Western contexts. A Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA)-guided search using Scopus and Google Scholar identified 26 relevant studies. The key findings showed the varied and crucial roles that HRMPs play in communicating change goals, engaging employees, and collaborating with stakeholders. In particular, hard OC involving actions such as downsizing warrants responsive HRMPs. Although some practices transfer well across settings, implementing HRMPs in non-Western environments requires adaptation to local cultural and religious norms. The predominant focus on Western contexts underscores the need for more research in understudied regions, such as the Middle East and North Africa. The limitations of this review include potential biases in the source studies and the exclusion of nonindexed literature. We conclude by calling for an expanded investigation into evidence-based HRMPs and the complex dynamics between HRMPs and diverse types of OC across different organizational and national settings.